Barabaro. - Progetto Giovani, Firenze; Flux, Liège (Firenze : Progetto Giovani, 1990)
Calonaci, Marco ; Lorusso, Nicola ; Magni, Marco ; Studio Multimages ; Ballerini, Patrizia ; Campisi, Tania ; Causa, Maria ; Landucci, Francesco ; Ortega, Manuel ; Amstutz, Colomba ; Jochamowitz, Lucy ; Lipartiti, Eva ; Parisi, Paolo ; Parlapiano, Luisa ; Pettini, Maurizio ; Querci, Alessandro ; Sparavigna, Virginio ; Stefanon, Gianantonio ; Stella, Salvatore ; Surace, Giovanni ; Bartolini, Piero ; Pantani, Lia ; Tamo, Miguela
Barabaro, Progetto Giovani, Firenze / Flux, Liège, 1990
boek